2020
DOI: 10.1016/j.energy.2020.118105
|View full text |Cite
|
Sign up to set email alerts
|

Flexible operation of supercritical coal-fired power plant integrated with solvent-based CO2 capture through collaborative predictive control

Abstract: This paper presents a controller design study for the supercritical coal fired power plant (CFPP) integrated with solvent-based post-combustion CO2 capture (PCC) system. The focus of the study is on the steam drawn-off from turbine to the re-boiler, which is the key interaction between the CFPP and PCC plants. The simulation study of a 660MW supercritical CFPP-PCC unit model has shown that the impact of re-boiler steam change on the power generation of CFPP is more than 100 times faster than that on the PCC op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Readers are referred to Refs. [ 5 , 6 , 7 , 8 , [9] , [10] , [11] , [12] , 13 , 14 , 15 , 16 ], [ [17] , [18] , [19] ], and these references provide further details on carbon dioxide (CO2) emissions and some recent advances in mathematical modeling and control strategies. But here we have examined an entirely new and different problem of Emission, diffusion, and uptake of air pollutants depending on different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Readers are referred to Refs. [ 5 , 6 , 7 , 8 , [9] , [10] , [11] , [12] , 13 , 14 , 15 , 16 ], [ [17] , [18] , [19] ], and these references provide further details on carbon dioxide (CO2) emissions and some recent advances in mathematical modeling and control strategies. But here we have examined an entirely new and different problem of Emission, diffusion, and uptake of air pollutants depending on different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It can even be economically beneficial by exploiting higher electricity prices during peak periods [21]. Several simulation based studies have investigated operational flexibility of coal-and gas-PCC, focussing on comparing operating strategies [22,23,24], developing process control strategies [25,26], and multi-period optimisation [27]. Montañés et al [28] identifies the operational requirements of flexible CO2 capture, and concluded future work should consist of validated dynamic process models evaluating various transient operating scenarios, to discover potential bottlenecks during flexible operation.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the CO 2 capture system of power plants with an MEA absorbent has the lowest economic cost of increasing the electricity at one time. By constructing a model of the post-combustion CO 2 capture system in Aspen Plus software, the simulation study of the capture system under different absorbents, absorption towers and de-absorption towers is carried out; the economic performance under the optimal process parameters selected is analyzed; and the design scheme is obtained in order to make the carbon capture rate the lowest it can be [7,8]. By optimizing the stable operating parameters of each process of CO 2 capture, [9,10] achieves the goal of minimizing the overall energy loss and economic operation of the system.…”
Section: Introductionmentioning
confidence: 99%